Self-Selecting Resistive Switching Scheme Using TiO2 Nanorod Arrays - Chi-Hsin Huang (Nature Portfolio, 2017)
Abstract In this study, the resistive switching scheme using TiO2 nanorod arrays synthesized by a large-scale and low-cost hydrothermal process was reported. Especially, the nonlinear I–V characteristics of TiO2 nanorod arrays with a nonlinearity of up to ~10, which suppress the leakage current less than 10−4 Acm−2, were demonstrated, exhibiting a self-selecting resistive switching behavior. It provides a simple pathway for integration of RRAM crossbar arrays without additional stacking of active devices. The mechanisms of the nonlinear resistive switching behaviors were discussed in detail. In addition, the maximum array numbers of 79 for self-selecting RRAM cells were estimated. The results demonstrate an opportunity of using the concept of self-selecting resistive switching characteristics in a single material, which offers a new strategy to tackle the sneak path issue of RRAM in the crossbar arrays structure.